Progressive multifocal leukoencephalopathy in HIV-infected patients: clinical features and diagnosis (literature review) - E. A. Samotolkina; A. V. Pokrovskaya; S. V. Matosova; E. A. Domonova (Журнал инфектологии)
Progressive multifocal leukoencephalopathy (PML) is one of the most severe opportunistic diseases of the central nervous system, which leads to multiple demyelination of brain structures, neurological symptoms and frequent death or disability of the patient. The etiological factor of this disease is Human polyomavirus 2 (JCPyV).This pathogen is widespread – antibodies are found in 80% of the world›s population. However, the clinical symptoms of this infection appear only in people with a pronounced decline in cellular immunity. Until 1980 progressive multifocal leukoencephalopathy was extremely rarely diagnosed. Now days the main cause of the clinical symptoms of PML is immunodeficiency caused by HIV infection. Clinical manifestations of PML are characterized by various non-specific neurological symptoms, similar to other lesions of the central nervous system, the symptoms progress slowly over several months, and usually lead to death. Diagnosis of PML is based on laboratory and instrumental methods, such as DNA JCPyV detection in the cerebrospinal fluid, brain biopsy, and radiation diagnostic methods. There is no effective prevention and etiotropic therapy for PML. Improved parameters of cellular immunity and antiretroviral treatment in HIV positive patients significantly increase the life expectancy of patients with PML. Despite the ability of drugs to prevent the progression of the disease, pathological changes in the brain are irreversible and lead to persistent disability of patients, therefore, it is necessary to diagnose PML in the early stages of the disease.